Advances in neuromodulation for treatment of dystonia - LIANG Nan; MA Ling⁃yan; MENG Fan⁃gang; ZHANG Jian⁃guo (Chinese Journal of Contemporary Neurology and Neurosurgery)
Dystonia is a group of movement disorders characterized by continuous or intermittent muscle contraction, causing abnormal movements and/or repetitive postures. It has the characteristics of diverse causes and complex clinical symptoms. As a reversible neurosurgical therapy, neuromodulation technique has achieved remarkable results in the clinical treatment of dystonia. This article reviews common neuromodulation technique in treatment of dystonia and looks forward to the technological innovation, multidisciplinary integration and clinical promotion prospects of neuromodulation, so as to provide a theoretical basis and new ideas for subsequent research and clinical application.